Mathematical modeling and hybrid heuristic for unequal size facility layout problem - Nordin, Nurul Nadia; Zainuddin, Zaitul Marlizawati; Salim, Sutinah; Ponnusamy, Raja Rajeswari (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2009)

(untitled)
The facility layout design has been regarded as the key to improve plant productivity, which are relevant to both manufacturing and service sectors. Facility Layout Problems (FLPs) are known to be NP-hard problems; various optimization approaches for small problems and heuristic approaches for the larger problems have been proposed to elucidate the problem. A mathematical model is developed for the unequal size facility layout problem with fixed flow between departments. We are considering the orientations of the departments with various sizes and aims to minimize the distance traveled by people, material, and other supporting services in the safest and most effective manner. Some of the constraints considered in the modeling are the restricted areas, reserved departmentry locations, and also the irregularity of the shapes of manufacturing layout. This paper focuses on the mathematical model and the solution of the non-quadratic assignment problem (non-QAP) by hybridizing the meta-heuristic methods i.e. Genetic Algorithm (GA) and Simulated Annealing (SA). This work could be used in future as a reference for those researchers interested in tackling this challenging unequal facility layout problem